# (2b-3)/7-b/2=(b+3)/14

## Simple and best practice solution for (2b-3)/7-b/2=(b+3)/14 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so dont hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

## Solution for (2b-3)/7-b/2=(b+3)/14 equation:

(2b-3)/7-b/2=(b+3)/14
We move all terms to the left:
(2b-3)/7-b/2-((b+3)/14)=0
We calculate fractions

(-98b^2)/()+2b/()+(-((b+3)*7*2)/()=0

We calculate terms in parentheses: +(-((b+3)*7*2)/(), so:
-((b+3)*7*2)/(
We multiply all the terms by the denominator

-((b+3)*7*2)

We calculate terms in parentheses: -((b+3)*7*2), so:
(b+3)*7*2

We calculate terms in parentheses: -((b+3)*7*2), so:
(b+3)*7*2

We calculate terms in parentheses: -((b+3)*7*2), so:
(b+3)*7*2

We calculate terms in parentheses: -((b+3)*7*2), so:
(b+3)*7*2

We calculate terms in parentheses: -((b+3)*7*2), so:
(b+3)*7*2

We calculate terms in parentheses: -((b+3)*7*2), so:
(b+3)*7*2

We calculate terms in parentheses: -((b+3)*7*2), so:
(b+3)*7*2

We calculate terms in parentheses: -((b+3)*7*2), so:
(b+3)*7*2

We calculate terms in parentheses: -((b+3)*7*2), so:
(b+3)*7*2

We calculate terms in parentheses: -((b+3)*7*2), so:
(b+3)*7*2

We calculate terms in parentheses: -((b+3)*7*2), so:
(b+3)*7*2

We calculate terms in parentheses: -((b+3)*7*2), so:
(b+3)*7*2

We calculate terms in parentheses: -((b+3)*7*2), so:
(b+3)*7*2

We calculate terms in parentheses: -((b+3)*7*2), so:
(b+3)*7*2

We calculate terms in parentheses: -((b+3)*7*2), so:
(b+3)*7*2

We calculate terms in parentheses: -((b+3)*7*2), so:
(b+3)*7*2

We calculate terms in parentheses: -((b+3)*7*2), so:
(b+3)*7*2

We calculate terms in parentheses: -((b+3)*7*2), so:
(b+3)*7*2

We calculate terms in parentheses: -((b+3)*7*2), so:
(b+3)*7*2

We calculate terms in parentheses: -((b+3)*7*2), so:
(b+3)*7*2

We calculate terms in parentheses: -((b+3)*7*2), so:
(b+3)*7*2

We calculate terms in parentheses: -((b+3)*7*2), so:
(b+3)*7*2

We calculate terms in parentheses: -((b+3)*7*2), so:
(b+3)*7*2

We calculate terms in parentheses: -((b+3)*7*2), so:
(b+3)*7*2

We calculate terms in parentheses: -((b+3)*7*2), so:
(b+3)*7*2

We calculate terms in parentheses: -((b+3)*7*2), so:
(b+3)*7*2

We calculate terms in parentheses: -((b+3)*7*2), so:
(b+3)*7*2

We calculate terms in parentheses: -((b+3)*7*2), so:
(b+3)*7*2

We calculate terms in parentheses: -((b+3)*7*2), so:
(b+3)*7*2

We calculate terms in parentheses: -((b+3)*7*2), so:
(b+3)*7*2

We calculate terms in parentheses: -((b+3)*7*2), so:
(b+3)*7*2

We calculate terms in parentheses: -((b+3)*7*2), so:
(b+3)*7*2

We calculate terms in parentheses: -((b+3)*7*2), so:
(b+3)*7*2

We calculate terms in parentheses: -((b+3)*7*2), so:
(b+3)*7*2

We calculate terms in parentheses: -((b+3)*7*2), so:
(b+3)*7*2

We calculate terms in parentheses: -((b+3)*7*2), so:
(b+3)*7*2

We calculate terms in parentheses: -((b+3)*7*2), so:
(b+3)*7*2

We calculate terms in parentheses: -((b+3)*7*2), so:
(b+3)*7*2

We calculate terms in parentheses: -((b+3)*7*2), so:
(b+3)*7*2

We calculate terms in parentheses: -((b+3)*7*2), so:
(b+3)*7*2

We calculate terms in parentheses: -((b+3)*7*2), so:
(b+3)*7*2

We calculate terms in parentheses: -((b+3)*7*2), so:
(b+3)*7*2

We calculate terms in parentheses: -((b+3)*7*2), so:
(b+3)*7*2

We calculate terms in parentheses: -((b+3)*7*2), so:
(b+3)*7*2

We calculate terms in parentheses: -((b+3)*7*2), so:
(b+3)*7*2

We calculate terms in parentheses: -((b+3)*7*2), so:
(b+3)*7*2

We calculate terms in parentheses: -((b+3)*7*2), so:
(b+3)*7*2

We calculate terms in parentheses: -((b+3)*7*2), so:
(b+3)*7*2

We calculate terms in parentheses: -((b+3)*7*2), so:
(b+3)*7*2

We calculate terms in parentheses: -((b+3)*7*2), so:
(b+3)*7*2

We calculate terms in parentheses: -((b+3)*7*2), so:
(b+3)*7*2

We calculate terms in parentheses: -((b+3)*7*2), so:
(b+3)*7*2

We calculate terms in parentheses: -((b+3)*7*2), so:
(b+3)*7*2

We calculate terms in parentheses: -((b+3)*7*2), so:
(b+3)*7*2

We calculate terms in parentheses: -((b+3)*7*2), so:
(b+3)*7*2

We calculate terms in parentheses: -((b+3)*7*2), so:
(b+3)*7*2

We calculate terms in parentheses: -((b+3)*7*2), so:
(b+3)*7*2

We calculate terms in parentheses: -((b+3)*7*2), so:
(b+3)*7*2

We calculate terms in parentheses: -((b+3)*7*2), so:
(b+3)*7*2

We calculate terms in parentheses: -((b+3)*7*2), so:
(b+3)*7*2

We calculate terms in parentheses: -((b+3)*7*2), so:
(b+3)*7*2

We calculate terms in parentheses: -((b+3)*7*2), so:
(b+3)*7*2

We calculate terms in parentheses: -((b+3)*7*2), so:
(b+3)*7*2

We calculate terms in parentheses: -((b+3)*7*2), so:
(b+3)*7*2

We calculate terms in parentheses: -((b+3)*7*2), so:
(b+3)*7*2

We calculate terms in parentheses: -((b+3)*7*2), so:
(b+3)*7*2

We calculate terms in parentheses: -((b+3)*7*2), so:
(b+3)*7*2

We calculate terms in parentheses: -((b+3)*7*2), so:
(b+3)*7*2

We calculate terms in parentheses: -((b+3)*7*2), so:
(b+3)*7*2

We calculate terms in parentheses: -((b+3)*7*2), so:
(b+3)*7*2

We calculate terms in parentheses: -((b+3)*7*2), so:
(b+3)*7*2

We calculate terms in parentheses: -((b+3)*7*2), so:
(b+3)*7*2

We calculate terms in parentheses: -((b+3)*7*2), so:
(b+3)*7*2

We calculate terms in parentheses: -((b+3)*7*2), so:
(b+3)*7*2

We calculate terms in parentheses: -((b+3)*7*2), so:
(b+3)*7*2

We calculate terms in parentheses: -((b+3)*7*2), so:
(b+3)*7*2

We calculate terms in parentheses: -((b+3)*7*2), so:
(b+3)*7*2

We calculate terms in parentheses: -((b+3)*7*2), so:
(b+3)*7*2

We calculate terms in parentheses: -((b+3)*7*2), so:
(b+3)*7*2

We calculate terms in parentheses: -((b+3)*7*2), so:
(b+3)*7*2

We calculate terms in parentheses: -((b+3)*7*2), so:
(b+3)*7*2

We calculate terms in parentheses: -((b+3)*7*2), so:
(b+3)*7*2

We calculate terms in parentheses: -((b+3)*7*2), so:
(b+3)*7*2

We calculate terms in parentheses: -((b+3)*7*2), so:
(b+3)*7*2

We calculate terms in parentheses: -((b+3)*7*2), so:
(b+3)*7*2

We calculate terms in parentheses: -((b+3)*7*2), so:
(b+3)*7*2

We calculate terms in parentheses: -((b+3)*7*2), so:
(b+3)*7*2

We calculate terms in parentheses: -((b+3)*7*2), so:
(b+3)*7*2

We calculate terms in parentheses: -((b+3)*7*2), so:
(b+3)*7*2

We calculate terms in parentheses: -((b+3)*7*2), so:
(b+3)*7*2

We calculate terms in parentheses: -((b+3)*7*2), so:
(b+3)*7*2

We calculate terms in parentheses: -((b+3)*7*2), so:
(b+3)*7*2

We calculate terms in parentheses: -((b+3)*7*2), so:
(b+3)*7*2

We calculate terms in parentheses: -((b+3)*7*2), so:
(b+3)*7*2

We calculate terms in parentheses: -((b+3)*7*2), so:
(b+3)*7*2

We calculate terms in parentheses: -((b+3)*7*2), so:
(b+3)*7*2

We calculate terms in parentheses: -((b+3)*7*2), so:
(b+3)*7*2

We calculate terms in parentheses: -((b+3)*7*2), so:
(b+3)*7*2

We calculate terms in parentheses: -((b+3)*7*2), so:
(b+3)*7*2

We calculate terms in parentheses: -((b+3)*7*2), so:
(b+3)*7*2

We calculate terms in parentheses: -((b+3)*7*2), so:
(b+3)*7*2

.ges-responsive-bottom-big { width: 300px; height: 250px; }
@media(max-width: 330px) { .ges-responsive-bottom-big { margin-left:-15px; } }
@media(min-width: 360px) { .ges-responsive-bottom-big { width: 336px; height: 280px; } }

See similar equations:

| (2b-3)/7-b/2=b+3/14 |
| 4s*4=64s= |
| 3n+12+23+4n=210 |
| 3n+15+2n+15=180 |
| 8n-8+4n=52 |
| 5x-(2x-10)=45 |
| -68=-4(5n+7) |
| 4(m-1)=-(1-4m) |
| 20.2+d=23 |
| 1x+10=-25+6x |
| 5x+9=-7x-111 |
| 20*1/5+d=23 |
| 7x-7=-1x-47 |
| 9(14-t=-117 |
| 30m+25=-20+1000 |
| 1x+1=-14-4x |
| 18=11v-8v |
| 9+3x=5x+103/11 |
| 4(3y-5)=13 |
| 1x+1=37-2x |
| 7x+7=-5x+19 |
| 7x+5=4x-25 |
| 5220=(n-2)180 |
| 9x-9=-7(x=1) |
| 36.75x+28.50=0.75x |
| 4(u+3)-6u=32 |
| 3^x-2=43 |
| 11-12-29=a |
| 6.2÷(2x+1)=21/3÷4 |
| 2x-3(2-8x)=2×+22 |
| 6.2÷(2x+1)=21	3÷4 |
| 6.2/(2x+1)=21/3/4 |
| 3(x-5)=4x-2(x+5) |
| 10x-4(3-5x)=2(5-x) |
| -9(y+9)=-40 |
| 3.1x=-5/12 |
| 1.6+0.4y+2y-(16)=0 |
| 10x+6(6-x)=2x-14 |
| 6(5x+4)-8=7+2(3-3x) |
| -25=-2(9a+6) |
| 82=42/x |
| 7n^2+2407n-45594=0 |
| -15=9d-5d |
| 2?x-5?^2=17 |
| 7(7-m)=105 |
| 1.6+0.4y+2y=16 |
| 5y-7+4y=22 |
| 4(3-x)-2(x-5)=4x+7(2x-5) |
| x-13.25=24.50 |
| 7(3x-2)-2(x-4)+3=0 |
| 2y-6.4=y+10 |
| 8n+4=4(2n+1) |
| 12x-4x=24 |
| 5/6=x/19 |
| 11x=3(x-3)-(x-8) |
| 12+6x÷3=5-9÷2 |
| 11/x=32/21 |
| 10/x=30/42 |
| (2x-15)+11x=??? |
| 6n+8=n-2 |
| x/12=55/132 |
| 6+7(b-1)=5+b |
| x/5=200/50 |
| 4(x+5)+4x+8=8(x+4) |
| 4/16=m/24 |

Equations solver categories

Equations solver - equations involving one unknown
Percentage Calculator - Step by step
Derivative calculator - step by step
Graphs of functions
Factorization
Greatest Common Factor
Least Common Multiple
System of equations - step by step solver
Fractions calculator - step by step
Theory in mathematics
Roman numerals conversion
Tip calculator
Numbers as decimals, fractions, percentages
More or less than - questions

.ges-responsive-left-big { width: 300px; height: 250px;}
@media(min-width: 360px) { .ges-responsive-left-big { width: 336px; height: 280px; } }
@media(min-width: 768px) { .ges-responsive-left-big { width: 300px; height: 600px; } }

2x-2=8

x-3=5

3x+2=18

2x+10=12

6x-2=14

3x=12

4x-2=12

9x-3=6

12+x=5

x+8=13

all equations

var _gaq = _gaq || [];
_gaq.push(['_setAccount', 'UA-31171154-1']);
_gaq.push(['_trackPageview']);

(function() {
var ga = document.createElement('script'); ga.type = 'text/javascript'; ga.async = true;
ga.src = ('https:' == document.location.protocol ? 'https://ssl' : 'http://www') + '.google-analytics.com/ga.js';
var s = document.getElementsByTagName('script')[0]; s.parentNode.insertBefore(ga, s);
})();

`